2005
DOI: 10.1038/sj.cdd.4401801
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the antioncogenic Chk2 kinase by the oncogenic Wip1 phosphatase

Abstract: The antioncogenic Chk2 kinase plays a crucial role in DNA damage-induced cell-cycle checkpoint regulation. Here we show that Chk2 associates with the oncogenic protein Wip1 (wild-type p53-inducible phosphatase 1) (PPM1D), a p53-inducible protein phosphatase. Phosphorylation of Chk2 at threonine68 (Thr68), a critical event for Chk2 activation, which is normally induced by DNA damage or overexpression of Chk2, is inhibited by expression of wild-type (WT), but not a phosphatase-deficient mutant (D314A) of Wip1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
175
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(184 citation statements)
references
References 37 publications
5
175
2
Order By: Relevance
“…While this manuscript was in preparation, Fujimoto et al (2005) published results similar to ours regarding the binding of Wip1 to Chk2 and the dephosphorylation of phospho-Thr68 . However, there are key differences in some of our results and interpretations.…”
Section: Wip1 Inhibits Chk2 Activation In X-irradiated Cellssupporting
confidence: 67%
See 3 more Smart Citations
“…While this manuscript was in preparation, Fujimoto et al (2005) published results similar to ours regarding the binding of Wip1 to Chk2 and the dephosphorylation of phospho-Thr68 . However, there are key differences in some of our results and interpretations.…”
Section: Wip1 Inhibits Chk2 Activation In X-irradiated Cellssupporting
confidence: 67%
“…However, there are key differences in some of our results and interpretations. Fujimoto et al (2005) did not determine whether or not IR stimulates the interaction of Wip1 and Chk2 within cells as we did. They also did not report dose-response analyses that allowed us to distinguish the increased catalytic efficiency and specificity of Wip1 towards phospho-Thr68 compared with the other Chk2 phosphorylation sites.…”
Section: Wip1 Inhibits Chk2 Activation In X-irradiated Cellsmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous analysis showed that Wip1 could modulate apoptotic response and proliferation (Bulavin et al, 2004;Belova et al, 2005), which could explain the early onset of tumors observed in MMTV-ErbB2/ PPM1D mice. While there was no significant difference in the rate of apoptosis between analyzed samples Several potential downstream targets of Wip1 have been identified in vitro: p38 MAPK, p53, Chk1, Chk2 and ataxia-telangiectasia mutated (ATM) (Takekawa et al, 2000;Lu et al, 2005;Fujimoto et al, 2006;Shreeram et al, 2006). The role of p38 MAPK is particularly interesting, as we previously found that Wip1-deficient mice show a p38 MAPK-dependent delay in the onset of breast cancer when crossed with MMTV-ErbB2 transgenic mice (Bulavin et al, 2004).…”
mentioning
confidence: 95%